1980
DOI: 10.1002/jmor.1051630309
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the otolithic membrane and otolith in the juvenile mummichog, Fundulus heteroclitus

Abstract: The sagitta otolithic membrane of Fundulus heteroclitus consists of two different zones. A structured zone (gelatinous layer), which usually exhibits a reticulated or honeycomb-like architecture, is composed of tightly arranged fibrous material and covers only the sensory region of the macula. The gelatinous layer extends from the otolith surface to the tips of the sensory hairs, and probably functions primarily as a mechanoreceptor. The arrangement of this zone is closely associated with specific overlying st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 26 publications
3
61
0
1
Order By: Relevance
“…The teleost OM consists of an upper gelantinous layer (OMg) and a lower filamentous, subcapular layer (OMsc) (24). Immunohistochemical analysis using affinity purified SC-reactive immunoglobulins indicated that the SC protein was uniformly dispersed throughout the gelatinous layer of the teleost OM.…”
Section: Discussionmentioning
confidence: 99%
“…The teleost OM consists of an upper gelantinous layer (OMg) and a lower filamentous, subcapular layer (OMsc) (24). Immunohistochemical analysis using affinity purified SC-reactive immunoglobulins indicated that the SC protein was uniformly dispersed throughout the gelatinous layer of the teleost OM.…”
Section: Discussionmentioning
confidence: 99%
“…Growth history of individual fish is recorded in the otolith (Degens et al 1969, Dunkelberger et al 1980, Watanabe et al 1982, Mugiya 1987. In this study, individual growth histories of larval bluefin tuna were back-calculated from the otolith increment width and compared to growth histories of juvenile bluefin tuna collected in the coastal zone of Japan.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Scombrids have a high growth rate in the larval stages, and this growth is potentially variable depending on water temperature and food availability, implying that small variations in larval growth may induce broad variations in cumulative mortality and recruitment of the stock. We examined the hypothesis that growth during the early larval period is a key factor in the survival process of Pacific bluefin tuna larvae.Growth history of individual fish is recorded in the otolith (Degens et al 1969, Dunkelberger et al 1980, Watanabe et al 1982, Mugiya 1987. In this study, individual growth histories of larval bluefin tuna were back-calculated from the otolith increment width and compared to growth histories of juvenile bluefin tuna collected in the coastal zone of Japan.…”
mentioning
confidence: 99%
“…Otoliths consist primarily of calcium carbonate and proteins that are continuously deposited onto the otolith surface over time and are not reabsorbed (Dunkelberger et al 1980, Wright et al 1991, Asano & Mugiya 1993, Takagi & Takahashi 1999.…”
Section: Introductionmentioning
confidence: 99%